Contribution of Gelatinase, Serine Protease, and fsr to the Pathogenesis of Enterococcus faecalis Endophthalmitis - Engelbert, Michael (American Society for Microbiology, 2004)
Gelatinase and serine protease were found to contribute in concert to pathogenesis in a rabbit model of endophthalmitis. However, a mutant defective in the fsr regulator was observed to be more attenuated than a mutant rendered defective in the expression of gelatinase and serine protease as the result of a polar transposon insertion into the former. This increased attenuation suggests that there are possible additional pleiotropic effects of the defect in fsr on expression of traits contributing to the pathogenesis of enterococcal infection.